A Genetic Algorithm to Obtain Consistency in Analytic Hierarchy Process - da Serra Costa, José Fabiano (2011)
This work presents a proposition to solve the problem of inconsistency in Analytic HierarchyProcess (AHP) matrices using genetic algorithms. Decision matrices resulting from an applicationof AHP can be considered an effective method to structure and represent relevant information ofa strategic problem. Inconsistency in the results is a real and frequent possibility. In this case, theresults obtained would become ineffective considering the objectives of the model, which meansno gains in decision making. The Genetic Algorithms are probabilistic search computer modelswhich are based on the mechanics of natural selection and genetics, combining the concepts ofselective adaptation and survival of the fittest. They are considered to be a powerful technique ofstochastic optimization and, probably the most important evolutionary computer techniques. Itsapplication to the AHP matrices case allows the detection of inconsistent matrices, while offersalternative solutions to the decision-maker.